Manajemen Pendidikan Berbasis Budaya Pesantren dalam Pembentukan Karakter Mahasiswa - Semin Semin (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2023)
This research is motivated by the urgency of character education in Indonesia and to find out the extent of Islamic boarding school cultural management in forming student character in the campus environment. This is based on the very serious problem of moral and character degradation which today not only affects children and teenagers, the majority of whom are still students. This is also starting to spread to universities. The shift in personality values ​​in various immoral behaviors is so clear and visible that it occurs in the midst of social life. Based on the conditions on the ground, the government was moved to reorganize Indonesia's education pattern with a character education program. Talking about management issues certainly cannot be separated from the activities of planning, organizing, staffing, coordinating, leading (facilitating, motivating, innovating), reporting, controlling. On the one hand, Islamic boarding schools as non-formal educational institutions are a space to prepare students in terms of requiring large and high-quality human resources (HR) to support the implementation of development programs well. the importance of effective educational management in shaping the character of students in creating a conducive educational environment. Through the habit of interacting well, the role of students as agents of change will be realized well, thereby providing enlightenment to the community in their environment. Based on this, it is fitting that graduates of Islamic Universities should truly be able to assume an identity as Muslim intellectuals of quality and moral character.